Isolated cysticercosis of anterior abdominal wall mimicking clinically as acute appendicitis: an unusual presentation - Gupta, MK; Ahmad, K; Ansari, S; Rauniyar, RK; Chaudhary, S (Journal of Universal College of Medical Sciences, 2014)
Cysticercosis, a parasitic disease caused by Taenia solium larva, is a major public health problem in developing countries. The encysted larval stage can affect any part of the body, but are most frequently detected in brain, eye, skeletal muscle and subcutaneous tissues. Isolated cysticercosis of the abdominal wall can rarely mimic acute abdomen due to its nonspecific clinical presentation. We report a case of isolated cysticercosis of the right lower abdominal wall in a 25-year-old female who presented with acute abdominal pain mimicking clinically as acute appendicitis. High resolution ultrasonography showed typical features of cysticercosis in the abdominal wall and the patient had excellent clinical response to albendazole. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9574 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 45-47